Forces Influencing Technical Mathematics Curriculum Implementation: Departmental Heads’ Understanding of Their Practices to Enact Roles and Responsibilities - Mfundo Mondli Khoza; Annatoria Zanele Ngcobo (Education Sciences)
This qualitative study explores forces influencing the practices of Departmental Heads (DHs) in enacting their roles in implementing and managing Technical Mathematics (TMAT) curriculum. TMAT was piloted in a few South African schools in 2016 and later scaled to others. Since its inception, learner performance has been uneven, raising questions about the processes of managing and implementing the curriculum. We use Samuel’s Force Field Model to understand forces influencing DH practices in their quest to implement and manage the curriculum. Data were generated using one-on-one interviews and document analysis and thematically analysed using NVivo. The findings reveal that contextual and external forces are the main factors that influence DH practices when it comes to the implementation and management of the curriculum. These forces influence practices such that the roles and responsibilities are carried out mainly for compliance purposes. While in theory, DHs seem to believe in collaboration, they prefer working in silos and perceive that the success of the TMAT curriculum implementation should be at the hands of seasoned mathematics teachers. In addition, they seem to consider curriculum implementation and management to be solely about ensuring curriculum coverage. We argue that to ensure the sustainability and effectiveness of the TMAT curriculum, there is a need for the continuous professional development of DHs, such that they are able to balance external forces and internal forces.